Consuming local vegetables from our local growers - Qingren Wang; Edward A. Evans; Margie Pikarsky; Teresa Olczyk (EDIS)
In recent years, consumers increasingly are seeking out locally grown foods, due to concern for freshness, food safety, and the carbon footprint associated with food sourced from distant places. This 5-page fact sheet promotes local vegetable consumption by pointing out some of the advantages, benefits, and business opportunities associated with local vegetable production and consumption. Written by Qingren Wang, Edward A. Evans, Margie Pikarsky, and Teresa Olczyk, and published by the UF Department of Horticultural Sciences, September 2014.